2014
DOI: 10.1002/chem.201404939
|View full text |Cite
|
Sign up to set email alerts
|

Expanded‐Ring N‐Heterocyclic Carbenes for the Stabilization of Highly Electrophilic Gold(I) Cations

Abstract: Strategies for the synthesis of highly electrophilic Au(I) complexes from either hydride- or chloride-containing precursors have been investigated by employing sterically encumbered Dipp-substituted expanded-ring NHCs (Dipp=2,6-iPr2 C6 H3 ). Thus, complexes of the type (NHC)AuH have been synthesised (for NHC=6-Dipp or 7-Dipp) and shown to feature significantly more electron-rich hydrides than those based on ancillary imidazolylidene donors. This finding is consistent with the stronger σ-donor character of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 97 publications
1
33
0
Order By: Relevance
“…Expanded‐ring NHCs, including those derived from six‐ and seven‐membered cyclic amidinium salts, are stronger σ‐donors than imidazolinylidenes,27 and their bonds to silver(I) are less labile than those of five‐membered NHCs 28. Six‐membered NHCs support the formation of rhodium(I) fluorides,29 and of μ‐hydrido‐ and μ‐chlorodigold cations formed via strongly electrophilic [(NHC)Au] + equivalents 30. We hoped that a more inert NHCAg bond would suppress the formation of homoleptic [L 2 Ag] + from the [(LAg) 2 (μ‐H)] + cation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanded‐ring NHCs, including those derived from six‐ and seven‐membered cyclic amidinium salts, are stronger σ‐donors than imidazolinylidenes,27 and their bonds to silver(I) are less labile than those of five‐membered NHCs 28. Six‐membered NHCs support the formation of rhodium(I) fluorides,29 and of μ‐hydrido‐ and μ‐chlorodigold cations formed via strongly electrophilic [(NHC)Au] + equivalents 30. We hoped that a more inert NHCAg bond would suppress the formation of homoleptic [L 2 Ag] + from the [(LAg) 2 (μ‐H)] + cation.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, the latter scenario is plausible, but the free energy for dissociation of H 2 from [(6 Me)Au(η 2 ‐H 2 )] + (6 Me is the N,N′ ‐dimethyl analogue of 6Dipp) has been calculated at +9.5 kcal mol −1 30. Because goldligand bonds are generally stronger than the corresponding silverligand bonds, we regard this figure as a rough upper boundary on the barrier for dissociation of H 2 from [LAg(η 2 ‐H 2 )] + 40.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Use of PhMe 2 SiH rather than Et 3 SiH gave only 6.A nX -ray crystal structure ( Figure 3) showed that 6 was mononuclear like 5,but that, in addition to aCu-H interaction, there was also one short Cu-C ipso contact (2.2183 (17) )tothe C 6 F 5 ring based on C29. [16] Then ature of this interaction differs noticeably from those found with more electropositive metals,w hich invariably involve ortho-C-F bond contacts.I np articular, the Cu-C ipso interaction in 6 was seen to be concomitant with lengthening of the B(1)-C(29) distance to 1.657(3) ,relative to the B(1)-C(23) and B1-C(35) distances of 1.624(3) and 1.628(3) , respectively.A dditionally,t he C 6Mes -Cu-H angle of 146.5(8)8 8 in 6 is notably more acute than that observed in 5 (162.8(14) 8 8).…”
mentioning
confidence: 75%
“…[15] Use of PhMe 2 SiH rather than Et 3 SiH gave only 6.A nX -ray crystal structure ( Figure 3) showed that 6 was mononuclear like 5,but that, in addition to aCu-H interaction, there was also one short Cu-C ipso contact (2.2183 (17) )tothe C 6 F 5 ring based on C29. [16] Then ature of this interaction differs noticeably from those found with more electropositive metals,w hich invariably involve ortho-C-F bond contacts.I np articular, the Cu-C ipso interaction in 6 was seen to be concomitant with lengthening of the B(1)-C(29) distance to 1.657 (3) Weaker donation to Cu in 6 is also manifest in ah igher computed positive charge at Cu (Figure 4b)and the reduced s B-H !Cu interaction which the NBO 2 nd order perturbation analysis quantifies as 42.9 kcal mol À1 .T he similar charges at Cu, Band Hin6 and the free [(6Mes)Cu] + and [HB(C 6 F 5 ) 3 ] À ions again suggest 6 is ab orate complex. An additional feature,a gain consistent with am ore electron deficient Cu center, is the presence of aC u-C ipso bond path which entails aring critical point associated with the {CuHBC ipso }unit.…”
mentioning
confidence: 90%
“…The[ LAu] + cation can be trapped by an equivalent of the NHCAuXp recursor to form Scheme19. [282] Theclosest to an isolable 4 ]. [395] Angewandte Chemie Reviews [{(NHC)Au} 2 (m-X)] + cations (where NHC = 6Dipp or 7Dipp; X = Ho rC l) when trying to remove the hydride by protonlysis with [H(OEt 2 ) 2 ][B(Ar CF3 ) 4 ]and chloride by abstraction with Na[B(Ar CF3 ) 4 ].…”
Section: Gold(i) Cationsmentioning
confidence: 99%